2016
DOI: 10.1007/s10067-016-3223-z
|View full text |Cite
|
Sign up to set email alerts
|

The functional PTPN22 C1858T polymorphism confers risk for rheumatoid arthritis in patients from Central Mexico

Abstract: Rheumatoid arthritis (RA) is a complex genetic disease. Human leukocyte antigen (HLA) and non-HLA genes are reportedly associated with an increased risk of RA. The protein tyrosine phosphatase non-receptor 22 gene (PTPN22), which encodes the lymphoid tyrosine phosphatase (LYP) protein, is one of the best examples of a non-HLA gene associated with a risk for RA in several populations. The functional PTPN22 C1858T (R620W) non-synonymous polymorphism is widely associated with an increased risk for RA in Europeans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Finally, 45 publication containing 23584 cases and 24497 healthy controls were identified as eligible publications for meta‐analyzing the association of the PTPN22 gene rs2476601 polymorphism and RA susceptibility. Of these 45 publication, 26 publications were conducted in Caucasians, 3,28–52 eight publications were in Asian countries, 53–60 seven publications were in African countries 61–67 and five publications were in countries with mixed ethnicity, which included Africans, Latins, American‐Africans and Caucasians 10,68–70 . Among the included studies, Rodriguez et al 46 evaluated the association of the PTPN22 gene rs2476601 SNP and RA in six countries (Spain, New Zealand, Norway, Germany, UK and The Netherlands), although the results were reported in one article; therefore, we enumerated this as one eligible publication.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 45 publication containing 23584 cases and 24497 healthy controls were identified as eligible publications for meta‐analyzing the association of the PTPN22 gene rs2476601 polymorphism and RA susceptibility. Of these 45 publication, 26 publications were conducted in Caucasians, 3,28–52 eight publications were in Asian countries, 53–60 seven publications were in African countries 61–67 and five publications were in countries with mixed ethnicity, which included Africans, Latins, American‐Africans and Caucasians 10,68–70 . Among the included studies, Rodriguez et al 46 evaluated the association of the PTPN22 gene rs2476601 SNP and RA in six countries (Spain, New Zealand, Norway, Germany, UK and The Netherlands), although the results were reported in one article; therefore, we enumerated this as one eligible publication.…”
Section: Resultsmentioning
confidence: 99%
“…Mexico City, located in central Mexico, is formed by approximately 50% Amerindian, 45% Caucasian, and 5% African ancestry (Martinez-Marignac et al, 2007). On the other hand, regions located in Western or Southeastern Mexico have a markedly different ethnic composition (Martínez-Cortés et al, 2012;Rincón et al, 2016). As far as we can tell, this is the first study showing an individual association (Hom et al, 2008) 70.2 (Huang et al, 2017) 13.1 (Sánchez et al, 2011) rs2736340C/T T allele 68.4 64.1 23.2 (Hom et al, 2008) 70.9 (Dang et al, 2016) 13.4 (Guthridge et al, 2014) BANK1 rs10516487G/A A allele 15.9 14.8 27.6 (Orozco el at., 2009) 13.9 (Dang et al, 2016) 26.0 (Martínez-Bueno et al, 2018) rs3733197G/A A allele 21.8 20.3 30.4 (Orozco et al, 2009) 22.0 (Huang et al, 2017) 21.5 (Bueno et al, 2018 between BANK1 rs1051648T/C and RA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study carried out in Mexico City (using autosomal ancestry-informative markers [AIMs]), it was identified that the individuals had 50% Amerindian, 45% Caucasian, and 5% African ancestry [40]. Meanwhile, individuals from Guadalajara and Morelia (both located in Western Mexico), and Culiacan (located in Northern Mexico) have a high percentage of European ancestry and a low percentage of Amerindian ancestry [19,20]. In another population like Yucatan (located in Southeastern Mexico), which presents a high Amerindian ancestry [20], this SLE-susceptibility locus has not been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Guadalajara and Morelia are located in Western Mexico; meanwhile, Culiacan is located in northern Mexico. These places are well known for having a high European ancestry (except Mexico City) and low Amerindian ancestry [19,20]. However, in populations with high Amerindian ancestry, like Yucatan (located southeast of Mexico) [20], ITGAM has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%